Notes on the National Economic Councils of Germany and France - Mortished, R. J. P. (Statistical and Social Inquiry Society of Ireland, 1929)
The Saorstat needs at least as much as any other State an organization designed to mobilize all available competences in the service of the State, to make a wide and penetrating review of our economic position and possibilities, to ensure the taking of long views and continuity and correlation in social and economic activities, to stimulate progress and, as a condition of all else, to educate the whole community and create a public opinion favourable to intelligent economic activity. These purposes might be served by the setting-up of a National Economic Council, not as a substitute for either Dail or Senate, but as a special organ of the State. The French and German models suggest possibilities of a body which would be an organ of study but also of advice, in equally close touch with Government and Parliament. But there would unquestionably be great difficulties. The insufficiency of economic organization, particularly on the employers' side, might perhaps render necessary an unusually extensive resort to nomination rather than delegation, though the existence of the Council would itself tend to cure this defect. But, since the phrase "National Economic Council" has already made some fugitive appearances in our public discussions, the first essential is to seek to give a real content to the phrase by such a presentation of working models as has been attempted in this paper.
Read before the Society on Friday, March 22nd, 1929
Keywords: German Economic Council; French Economic Council; 314.15